Bifurcation control of high-dimensional nonlinear chemical processes using an extended washout-filter algorithm. (4th January 2016) - Zhang, Nan; Seider, Warren D.; Chen, Bingzhen
Highlights: Design framework to modify bifurcation characteristics of nonlinear processes. Three modes of optimization formulations to extend conventional washout filters. Flexible relocation of Hopf points and desirable assignments of eigenvalues. Semi-global stabilization of high-dimensional NMRP CSTR process. Stabilization of desired solution branches under disturbances and uncertainties. Abstract: This paper presents a design framework to modify the bifurcation characteristics and stability of high-dimensional, nonlinear, chemical processes within specified operating regions. Portions of solution branches are stabilized and oscillatory process dynamics in the vicinity of Hopf bifurcation points (HBPs) are attenuated. A new optimization algorithm is introduced to circumvent the limitations of traditional washout filters for feedback control. This controller is used to operate a high-dimensional, nitroxide-mediated, radical polymerization (NMRP) in a continuous-stirred-tank reactor (CSTR). The algorithm adjusts the eigenvalues of the model Jacobian matrix to relocate the HBPs. It is shown to permit flexible modifications of the bifurcation characteristics, providing acceptable performance for set-point tracking and disturbance rejection, and stabilizing solution branches in specified regions.